PENGARUH GOOD CORPORATE GOVERNANCENCE TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan-Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2014-2018) - Rifda Ramadhanty; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2022)
This study aims to obtain empirical evidence about the effect of tax avoidance proxied through effective tax rate (ETR) on Good Corporate Governance. The elements of Good Corporate Governance used in this study are executive compensation, executive character, firm size, institutional ownership, independent commissioners, audit committee, and audit quality. The approach used in this study is quantitative approach. The data for this study were taken from annual and financial reports of manufacturing companies listed on the IDX in 2014-2018. Total of 211 samples of companies used in this study were obtained through purposive sampling technique. The data were analyzed using multiple analysis regression method. The results of this study empirically show that institutional ownership and audit quality have a significant positive effect on tax avoidance. Firm size has a significant negative effect. Meanwhile, executive compensation, executive character, independent commissioners, and audit committee are not significant on tax avoidance.